2015
DOI: 10.5114/kitp.2015.50560
|View full text |Cite
|
Sign up to set email alerts
|

CARDIAC SURGERY Evaluation of brain lesions in patients after coronary artery bypass grafting using MRI with the emphasis on susceptibility-weighted imaging

Abstract: IntroductionPatients undergoing coronary artery bypass grafting (CABG) are at risk of strokes and neurocognitive disorders.The aim of the studyThe aim of the study was to assess the clinical utility of susceptibility-weighted imaging (SWI) MRI in detection of new brain lesions in patients after CABG. We assessed the incidence and types of brain lesions and correlated the data with neurological examinations in groups of patients who underwent on-pump and off-pump CABG.Material and methodsPatients underwent a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This finding supports neuropathological reports from the early era and is consistent with the notion that HTx recipients have a high lifetime cumulative risk of cerebrovascular pathology. The extent of individual cerebrovascular pathology reflects the sum of minor and major cerebrovascular events that occurred before, during, and after successful HTx, including cardiac arrest, cerebral bleeding/infarction, as well as undesirable consequences of medical procedures (eg, left heart catheterization, former cardiac surgery), underlying disease, and comorbidities (eg, coronary heart disease, diabetes mellitus, hypertension).…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports neuropathological reports from the early era and is consistent with the notion that HTx recipients have a high lifetime cumulative risk of cerebrovascular pathology. The extent of individual cerebrovascular pathology reflects the sum of minor and major cerebrovascular events that occurred before, during, and after successful HTx, including cardiac arrest, cerebral bleeding/infarction, as well as undesirable consequences of medical procedures (eg, left heart catheterization, former cardiac surgery), underlying disease, and comorbidities (eg, coronary heart disease, diabetes mellitus, hypertension).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up MRI examinations were available for 56 patients with a median time after first postinterventional scan of 6 months (interquartile range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 91.1% (51/56) of those, there was no further increase in SWI lesions (Figure 2).…”
Section: Further Follow-up Mri Scansmentioning
confidence: 99%
“…Another study showed that SWI lesions occur after coronary bypass surgery, but only when CPB was used and with a similar frequency. 13 It is known that the CPB circuit may contain air emboli and/or microparticles, which may also be detected using transcranial Doppler ultrasound. 26 However, it is rather unlikely that the postoperative SWI lesions are mainly caused by air since they were also detectable 6 weeks after surgery.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%
See 1 more Smart Citation
“…Как правило, у пациентов соответствующей возрастной категории нередко выявляются атрофические изменения вещества мозга, чему соответствует расширение полостной системы мозга и проявления церебральной микроангиопатии в виде феномена лейкоареоза. Лейкоареоз -это нейровизуализационный симптом в виде обычно симметричных двусторонних диффузных изменений белого вещества головного мозга с понижением плотности на КТ-изображениях или изменением сигнала на МР-изображениях [1][2][3][4]. По локализации лейкоареоз делится на перивентрикулярный и субкортикальный: перивентрикулярный лейкоареоз представлен в виде изменений по периметру боковых желудочков, субкортикальный лейкоареоз имеет вид рассеянных очагов или очагов сливного характера.…”
Section: Introductionunclassified